The Disc Origin of the Milky Way Bulge. (28th June 2016) - Di Matteo, P.
Abstract: The Galactic bulge, that is the prominent out-of-plane over-density present in the inner few kiloparsecs of the Galaxy, is a complex structure, as the morphology, kinematics, chemistry, and ages of its stars indicate. To understand the nature of its main components—those at [Fe/H] ≳ −1 dex—it is necessary to make an inventory of the stellar populations of the Galactic disc(s), and of their borders: the chemistry of the disc at the solar vicinity, well known from detailed studies of stars over many years, is not representative of the whole disc. This finding, together with the recent revisions of the mass and sizes of the thin and thick discs, constitutes a major step in understanding the bulge complexity. N-body models of a boxy-/peanut-shaped bulge formed from a thin disc through the intermediary of a bar have been successful in interpreting a number of global properties of the Galactic bulge, but they fail in reproducing the detailed chemo-kinematic relations satisfied by its components and their morphology. It is only by adding the thick disc to the picture that we can understand the nature of the Galactic bulge.